2019
DOI: 10.31557/apjcp.2019.20.8.2287
|View full text |Cite
|
Sign up to set email alerts
|

Identification of High-Affinity Small Molecule Targeting IDH2 for the Clinical Treatment of Acute Myeloid Leukemia

Abstract: According to the American Cancer Society (ACS), Acute Myeloid Leukemia (AML) is a group of hematological diseases, phenotypic and genetically heterogeneous, characterized by clonal expansion of myeloid with diminished capacity for differentiation. It is characterized by the fast growth of white blood cells, red blood cells, platelets, and it's a build-up in the bone marrow restricting the production of traditional blood cells. Once healthy bone marrow cells are replaced with the leukemic cells, it results in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…In the context of the presence of the drug Enasidenib, we performed RUNX1: DNA-docking interactions employing the AML-associated RUNX1 mutants R142K, D171N, R174Q, P176H, R177Q in comparison to wild type (WT) RUNX1. Interestingly, we found that the docking scores of each of the RUNX1 mutants with Enasidenib was better than that with wild-type RUNX1, with R174Q and R177Q mutants having the highest ΔΔG values ( Figure 5C ), similar to that modeled for the docking of Enasidenib with its established target protein IDH2 ( Sweta et al, 2019 ). Thus, we speculate that at least certain cancer-associated mutations in RUNX1B may exhibit the capacity to alter drug binding, and thereby facilitate drug binding to the RUNX1 protein.…”
Section: Resultssupporting
confidence: 59%
“…In the context of the presence of the drug Enasidenib, we performed RUNX1: DNA-docking interactions employing the AML-associated RUNX1 mutants R142K, D171N, R174Q, P176H, R177Q in comparison to wild type (WT) RUNX1. Interestingly, we found that the docking scores of each of the RUNX1 mutants with Enasidenib was better than that with wild-type RUNX1, with R174Q and R177Q mutants having the highest ΔΔG values ( Figure 5C ), similar to that modeled for the docking of Enasidenib with its established target protein IDH2 ( Sweta et al, 2019 ). Thus, we speculate that at least certain cancer-associated mutations in RUNX1B may exhibit the capacity to alter drug binding, and thereby facilitate drug binding to the RUNX1 protein.…”
Section: Resultssupporting
confidence: 59%
“…A post dock study included energy minimization and Hbond optimization. Simplex Evolution was xed at max steps 300 and neighbor distance faster 1.00 [59][60][61][62][63][64][65]. Nelder Mead Simplex Minimization (using non-grid force eld and H-bond directionality) was applied after the docking to minimize the complex energy of ligand-receptor interaction [66-71].…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Therefore, researchers develop target-specific SMIs targeting critical malignant pathways. The combination of SMIs with clinical chemotherapy agents may increase treatment efficiency [15,16].…”
Section: Small Molecule Inhibitors In Lymphomamentioning
confidence: 99%